Human Computer Interaction: Simple Design and Principles - Usha, M (International Journal of Computer Sciences and Engineering, 2025)
Human-Computer Interaction explored the outline and use of computer technology, engaged on interface between people and the computers. This interface begins with the interaction between computers and human intends to show the powerful benefits of an user oriented approach to design the modern computer system. When the concept of interface begins to come into sight, it is universally understood as the hardware and software through which a human and computer can communicate. The interface can be taken as distinct or tangible, that developer can plan describe design, implement and append to the existing functions. Furthermore it balances, the technical and cognitive issues required for understanding the delicate interplay between people and computers, specifically in emerging fields like multimedia, virtual environment and computer supported cooperative work. Recent advancements in various signal processing technology such as speech, vision based gesture recognition, eye tracking, etc. are nowadays, successfully embedded to the systems. Still researches are going on to and needed for interpreting and fusing multiple sensing modalities in the context of HCI. Human-Computer Interaction (HCI) is a discipline concerned with the design, analysis, and executes of interactive computing system, along with appropriate theoretical methods and models is described here. The basic design and its principles of HCI are discussed.